Trends in Colloid and Interface Science XII
DOI: 10.1007/bfb0118046
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of two-dimensional colloidal crystals in confined geometry

Abstract: . The great advantage of colloidal systems are their convenient time (rnilliseconds) and length scajes (microns) which allow the observation of single particle trajectories and the variety of available interaction potentials.In this paper we present experimental data on the structure and dynamics of laterally confined 2D colloidal systems consisting of large superparamagnetic spheres lying on a smooth polymer substrate. A similar system has been already used by Zahn et al. [4] for the investigation of melting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 9 publications
1
32
1
Order By: Relevance
“…Additionally, most observed clusters had a coupling parameter that would refer to the solid state of a corresponding extended crystal. 5 In this phase, the diffusion coefficient of a colloidal dipole crystal scales only weakly with G, whereas signicant differences between angular and radial diffusion were found for clusters in hard-wall pots at low G. 25,45 In Fig. 7(a), angular diffusion D para…”
Section: Transport Coefficient From Inmmentioning
confidence: 91%
“…Additionally, most observed clusters had a coupling parameter that would refer to the solid state of a corresponding extended crystal. 5 In this phase, the diffusion coefficient of a colloidal dipole crystal scales only weakly with G, whereas signicant differences between angular and radial diffusion were found for clusters in hard-wall pots at low G. 25,45 In Fig. 7(a), angular diffusion D para…”
Section: Transport Coefficient From Inmmentioning
confidence: 91%
“…15,20 The B-field dependence of the magnetic moment is well known to correspond to the Langevin function. For the magnetic fields as used in this work, however, the magnetic moment increases in a linear way with B.…”
Section: Methodsmentioning
confidence: 99%
“…For small numbers of particles, the system does not crystallize in a triangular lattice as known for infinite systems (Wigner crystal) [11][12][13][14] but the structure of finite clusters is dominated by the geometry of the confining boundary. 15 In circular cavities, e.g. the particles form a concentric shell structure.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Furthermore, the study of confined self-assembly has revealed many interesting phenomena which depend on the nature of the confinement. [14][15][16][17][18][19][20][21] In the current study we will investigate the self-assembly of magnetorheological (MR) fluids in microfluidic confinement and the important role of channel topology.…”
Section: -4mentioning
confidence: 99%
“…In 2D cavities, the system boundaries define a finite closed area in which colloidal assembly takes place. 18,19 While this is a model system for studying the effects of closed boundaries upon self-assembly it is not practical for microfluidic applications. In 2D channels, the system remains open along one dimension and the colloids selfassemble between the two parallel closed boundaries defining the channel walls.…”
Section: -4mentioning
confidence: 99%